Duration of Antibiotic Therapy for Critically Ill Patients with Bloodstream Infections: A Retrospective Cohort Study - Thomas C Havey; Robert A Fowler; Ruxandra Pinto; Marion Elligsen; Nick Daneman (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: The optimal duration of antibiotic treatment for bloodstream infections is unknown and understudied.